Pengaruh Return on Asset (ROA) dan Earning Per Share (EPS) Terhadap Harga Saham Pada PT Indofood Sukses Makmur Tbk Periode 2011-2020 - Endang Nurita (Jurnal EMT KITA, 2022)
This study was conducted to determine whether the short Return on Assets ROA affect the stock price, whether the Earning Per Share which is abbreviated as EPS affect the stock price, and whether the ROA and EPS simultaneously affect the stock price which is carried out on the object of research at PT Indofood Sukses. Makmur Tbk for the period 2011-2020 for 10 years. This study uses a quantitative-based method and the tests carried out are classical assumption test, regression equation regression, coefficient of determination and hypothesis testing consisting of T and F. This research results that partially ROA has no effect on stock prices, partially EPS has an effect on the stock price and simultaneously ROA and EPS affect the stock price at PT Indofood Sukses Makmur TBK which occurred over a period of 10 years, from 2011 to 2020.